The Future of the European Union is Closely Related to a Stronger Economic Cooperation between Member States - Andreea Drăgoi (Revista de Economie Mondială, 2013)
Since the onset of the crisis in the euro area, the EU has implemented a series of measures to respond to the major economic challenges and support the efforts to boost growth and create jobs in the Member States. In October 2012, EU leaders have decided that in order to overcome the challenges brought by the sovereign debt crisis is necessary to establish a closer economic cooperation between European countries. Our paper aims to analyze the main measures taken at European level to converge toward this goal, aiming to highlight the extent to which they are "successful steps" leading to the creation of banking, fiscal and economic union in Europe.